Analysis of leaf morphology development-related genes and photosynthetic metabolic pathways in the transcriptomes of new leaves of Tea-Oil tree (Camellia oleifera ‘changlin53’) - Zongshun Zhou; Chuansong Chen; Ying Jiang; Yikai Hua; Yisi Liu; Hang Wang; Lixian Cao; Shuhua Wu; Hongyan Guo (PLoS ONE, 2026)
Camellia oleifera is a distinctive woody oilseed species endemic to southern China and is considered one of the world’s four major woody oil plants alongside oil palm, olive, and coconut. Its oil is renowned for its high content of unsaturated fatty acids, earning it the title “Oriental Olive Oil.” However, the conventional C. oleifera industry faces challenges such as substantial yield fluctuations and poorly understood regulatory mechanisms of oil metabolism. There is an urgent need to elucidate the synergistic mechanisms between photosynthetic efficiency and metabolic networks at the molecular level during leaf development to establish a theoretical foundation for high-yield, high-quality breeding. In this study, we systematically analyzed the developmental dynamics of new leaves at the spreading, growth, and maturity stages in the high-yield variety ‘Changlin 53’. By integrating morphological and anatomical observations with multi-period transcriptome sequencing, we investigated the key regulatory networks underlying leaf functional maturation. The results showed that as leaves developed, chlorophyll *a* content increased significantly, the expression of photosynthesis-related genes (e.g., chlorophyll *a*-binding protein Lhca1, photosystem II reaction center protein PsbA) was upregulated, photosynthetic capacity was gradually enhanced, and leaf functional maturation was promoted through the regulation of carbon assimilation and energy metabolism pathways. To validate these findings, 12 randomly selected differentially expressed genes (DEGs) were analyzed using qRT-PCR. The expression patterns were highly consistent with the RNA-Seq data. This study reveals, for the first time, the potential synergistic mechanism involving photosynthesis, metabolism, and hormones during leaf development in ‘Changlin 53’, providing a key theoretical basis for selecting and breeding C. oleifera varieties with high light-use efficiency.